HAEMATOLOGICAL AND BIOCHEMICAL PROFILE OF Clarias gariepinus FROM OPI LAKE IN NSUKKA LOCAL GOVERNMENT AREA, ENUGU STATE - Melefa, Temitope Dadewura; Okoloye, Uchechukwu (FUDMA JOURNAL OF SCIENCES, 2023)
Haematological and biochemical analysis have been recognized as helpful tools for monitoring fish health. The objective of the study was to investigate the reference value for the haematological and the biochemical profile of Clarias gariepinus from Opi Lake, Nsukka Local Government Area of Enugu State, Nigeria. A total of thirty samples of Clarias gariepinus comprising twelve males and eighteen females were obtained from the Lake. The blood samples were collected and analysed to obtain the haematological and biochemical parameters using standard methods. The results show that the haematological profile of Clarias gariepinus from Opi Lake were significantly different (p<0.05) between male and female. The result of the biochemical analysis was also influenced by sex, as the serum aspertate aminotranferase (AST) and alanine aminotransferase (ALT) were significantly higher in females than males. The results of this study provide useful information for comparative studies and also for water quality and fish health status monitoring.